Synthesis and characterization of Novel Schiff bases and evaluation of Corrosion inhibitors and biological activity - Ahmed M. Jassim (University of Thi-Qar Journal of Science, 2019)
Novel Schiff bases have been prepared from (6R,7R)-3-[( acetyloxy)methyl]-7-[[( Z)-2-(2aminothiazol-4-yl)-2-(methoxyimino)acetyl]amino]-8-oxo-5-thia-1-azabicyclo[4.2.0]-oct-2-ene-2carboxylatesodium and 2,4-dihydroxy benzaldehyde ,3-methoxy-4-hydroxy benzaldehyde and3,4dimethoxybenzaldehyde .The homogeneity of the compounds was chered by TLC .The structures ofthese Schiff bases have been characterized using IR,UV-Vis Spectroscopy, Elemental analysis(CHNS),melting points uncorrected ,These Schiff bases have been studies as Corrosion inhibitors for brass inacide media (0.5 N HCl) and antibacterial of the Schiff bases have also been tested against both GrampositiveandGram–nagativebacteria.